1993
DOI: 10.1246/bcsj.66.999
|View full text |Cite
|
Sign up to set email alerts
|

Five Types of J-Aggregates in Single-Chain Merocyanine Langmuir Monolayers on an Aqueous Subphase

Abstract: The formation of J-aggregates in Langmuir monolayers of a neat merocyanine dye (3-carboxymethyl-5-[2-(3-octadecyl-2-benzothiazolinyldene)ethylidene]-2-thioxo-4-thiazolidinone) has been examined by measuring the normal incidence absorption spectra. Five types of J-aggregates were found to be formed, depending on the temperature and the concentration and type of cations present in the subphase. The shift in the absorption peak wavelength on the J-aggregates formation is accounted for in terms of the number and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…Together with a broad band at 500−550 nm (abbreviated as band D), a distinct red-shifted band near 605 nm is observed for the mixed films, indicating the formation of J-aggregates in the mixed systems. On the other hand, the band D is dominant in the pure film and only a small J-band can be detected, similar to the spectra for either pure DS films or DS films mixed with FA and prepared at an air−“pure water” interface. ,,, Therefore, the atmosphere used for the LB deposition is crucial for obtaining J-aggregates of DS without metallic or ammonium cations in the DS−FA binary mixed systems.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…Together with a broad band at 500−550 nm (abbreviated as band D), a distinct red-shifted band near 605 nm is observed for the mixed films, indicating the formation of J-aggregates in the mixed systems. On the other hand, the band D is dominant in the pure film and only a small J-band can be detected, similar to the spectra for either pure DS films or DS films mixed with FA and prepared at an air−“pure water” interface. ,,, Therefore, the atmosphere used for the LB deposition is crucial for obtaining J-aggregates of DS without metallic or ammonium cations in the DS−FA binary mixed systems.…”
Section: Resultssupporting
confidence: 55%
“…J-aggregates in Langmuir−Blodgett (LB) films of merocyanine dyes, especially 3-carboxy-methyl-5-[2-(3-octadecylbenzothiasolin-2-ylidene)-ethylidene]rhodanine (abbreviated as DS and shown in the inset of Figure ), have attracted much attention because of their interesting properties, such as photoconduction, , in-plane anisotropy, , thermo- and chemichromism, , and nonlinear optics. , The formation mechanism of the J-aggregates has also been studied in LB films of DS and other merocyanine dyes. ,, As for the pure DS system, which bears one alkyl chain and one carboxylic group, Iriyama et al reported that the J-band is much more distinct on a Cd-containing buffer solution than on pure water, although they could detect a small J-band on pure water. Therefore, buffer solutions containing metal or ammonium cations are commonly used as the subphase for the LB deposition of DS. An exception to this is the well-developed J-band that has been reported for LB films of a 1:1:1 ternary mixture of DS, fatty acids (FA), and hexadecane, prepared on pure water . However, to our knowledge this ternary system has not been well characterized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the formation and the polymorphic behavior of the J aggregates of DS and DSe can be controlled by changing the temperature, surface pressure, or chemical composition of the subphase, and by mixing inert surfactant such as FA. [22][23][24][25][26][27][28]50,51,58 Sugi et al 14 reported that LB films of a DS-FA mixture prepared with a Cd 2ϩ -containing subphase exhibit clear polymorphic behavior upon secondary treatments with basic vapor, while those of a 6MeDS-FA mixture do not. These facts reflect the instability of the molecular arrangements in the J aggregates of DS and DSe.…”
Section: Models For Molecular Arrangementsmentioning
confidence: 99%
“…One of them fabricates monolayers of the pure merocyanine dye using an aqueous subphase containing metal or ammonium cations. 4,12,16,17 The other approach builds-up mixed monolayers of merocyanine and fatty acids (and/or other appropriate components) on a pure water subphase. 11,18 Several studies combining the two approaches have been also reported.…”
Section: And Ref 4)mentioning
confidence: 99%